Foreign Trade and Economic Growth of Nepal: An ARDL Approach - Acharya, Ramesh (Economic Review of Nepal, 2019)
Nepal is a developing country having high degree of trade openness. Trade volume is highly increased and imports always dominated exports. Therefore, the key objective is to find out contribution of foreign trade to the economic growth of Nepal. Level data are not stationary so first difference data are used for regression analysis. Thus, ARDL technique is used for the estimation. The study shows total trade and foreign direct investment has significant determinant of Gross Domestic product that is economic growth in Nepal both in short run and long run. The Study shows foreign trade plays the significant role for the economic growth of Nepal. One percent raise in foreign trade (total trade) brings 0.62 percent raise in gross domestic production.